Microalga as biofertilizer improves yield, sugars and amino acids content in red beets - Novaski, Aline; Mógor, Átila Francisco; Amatussi, Juliana Oliveira; Mógor, Gilda (Comunicata Scientiae, 2024)
The growing uncertainty of future changes in our global climate may pose a threat to some traditional farming methods, stimulating the development of nature friendly technologies. Microalgae are a group of micro photosynthetic organisms, which have immense potential as a renewable and ecofriendly bioresource for various industries. The present study was developed to evaluate foliar sprays of a green microalga Asterarcys quadricellulare (CCAP 294/1) on organically grown red beets (Beta vulgaris L) A field experiment was implemented to evaluate microalgal biomass bioactivity and its effects in leaves and hypocotyl growth, comparing fresh and dry weight, yield; and biochemical alterations, comparing pigments, sugars and free amino acids. The spray dried biomass of the A. quadricellulare was applied to leaves at concentrations 0.05g, 0.1 g, 0.15g and 0.25 g L-¹. The sprays with the microalga biomass increased yield, and improved free amino acids, sugars, dry weight and beets commercial diameter. This study shows that the foliar sprays presented a biofertilizer effect, emphasizing the solution at 0.25 g L-¹, which resulted in a 52% increase in yield. The results indicate that the microalga is a nature friendly, renewable and economic resource for red beet production.